2018
DOI: 10.1007/s00535-018-1469-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumor localization on the outcomes of surgery for an intrahepatic cholangiocarcinoma

Abstract: HICC shows more frequent bile duct invasion and lymph node metastasis, requires more extensive surgery, and has a higher rate of non-curative resection than PICC. However, if curative resection is achieved, the survival outcomes are expected to be equivalent between HICC and PICC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…Interestingly, on multivariate analysis the hilar involvement was not associated with survival, which was instead dictated by biological tumor characteristics, such as T stage, nodal status and tumor differentiation (1). Similar results were also reported by Orimo et al, who showed that hICC had more aggressive biological behavior with lower survival than pICC (5 years OS: 30.4% vs. 51.1%) (53).…”
Section: Postoperative Outcomes and Predictors Of Prognosissupporting
confidence: 76%
“…Interestingly, on multivariate analysis the hilar involvement was not associated with survival, which was instead dictated by biological tumor characteristics, such as T stage, nodal status and tumor differentiation (1). Similar results were also reported by Orimo et al, who showed that hICC had more aggressive biological behavior with lower survival than pICC (5 years OS: 30.4% vs. 51.1%) (53).…”
Section: Postoperative Outcomes and Predictors Of Prognosissupporting
confidence: 76%
“…R0 resection can be achieved in most peripheral ICC, thus achieving a good prognosis. 19,20 Therefore, visceral peritoneum invasion may not have any survival impact on ICC patients. As a consequence, the T3 category was deleted from the 8th edition and the T category was regrouped in the new mTNM staging.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with a higher NLR are more likely to develop LNM in malignant tumors, such as gastric cancer (33), colorectal cancer (34), esophageal cancer (35), and small cell lung cancer (36). Cumulative studies have shown that among HCC patients, the larger the tumor diameter is, the higher the probability of LNM (37), which may be related to the biological invasive ability of the tumor; this conclusion has also been con rmed in studies of malignant tumors such as intrahepatic cholangiocarcinoma (38) and gastric cancer (39).…”
Section: Discussionmentioning
confidence: 77%